Collaboration in Learning: Transcending the classroom walls
With the classroom at center stage in Collaboration in Learning, authors Mal Lee and Lorrae Ward look beyond the bygone era when schools operated within a paper-based, silo-effected, educational paradigm. In its place is a new mode of teaching, one in which there is no boundary between schools, teachers, students, parents, and the wider community. And, while the single most important denominator in this revolutionary shift is technology, this book is about far more - a resource that dissects what actually happens when the use of the digital is normalized, when every teacher in a school employs the digital as a natural part of their everyday teaching regime. With case studies from a diverse range of schools - from the US, the UK, Australia, and New Zealand - the emerging trend is one of authentic, enquiry-based learning. In this networked era, there exists an enhanced awareness and deeper appreciation of the learning that occurs in all aspects of a student's life, 24 hours a day, 7 days a week - and of the value of that learning in a formal educational context and beyond. The results are a greater personalization of learning, a richer school-based environment, and greater collaboration between home and school. The benefits for teachers, students, parents, and communities - learners one and all - can be said to transcend the classroom walls, and are as enduring as they are profound. Collaboration in Learning also includes a 'benefits realization' chapter, gaining currency from the corporate sector as a program management tool, adapted here to the school environment. The book reinforces a holistic focus on collaboration in learning, with the learner at the center, rather than a traditional 'top-down' teaching methodology. It consolidates the message in the book Bring Your Own Technology and stands as an independent yet complementary title.